STRATEGIC FORMULATION OF EDUCATION AT THE ISLAMIC HIGHER EDUCATION INSTITUTION AL BADAR CIPULUS - Dwi Ajeng Maulidya Makalao; Asy'ari Asy'ari; Badrudin Badrudin; Anggi Rahmah Fadilah; Anti Dewi Astuti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to analyze the strategic formulation of education at Sekolah Tinggi Agama Islam (STAI) Al Badar Cipulus, focusing on how Islamic values are integrated into modern strategic management principles to achieve institutional sustainability and competitiveness. Using a qualitative descriptive approach, data were collected through interviews, documentation, and observation involving institutional leaders directly engaged in the strategic planning process. Data analysis employed Miles and Huberman’s model, including condensation, display, and conclusion drawing to identify key themes in vision mission formulation, strategy selection, and institutional alliances. The findings show that the formulation of vision, mission, and strategic goals (VMSG) at STAI Al Badar is conducted through a participatory mechanism grounded in the values of Ahlussunnah wal Jama’ah An-Nahdliyah, emphasizing moderation, inclusiveness, and adaptability. The institution implements a combined differentiation and cost-efficiency strategy while upholding Islamic work ethics of amanah (trustworthiness) and ihsan (excellence). Furthermore, program diversification and strategic alliances through the establishment of a Campus Owned Business Entity (BUMK) and collaborations with other institutions strengthen financial sustainability and institutional reputation. The study concludes that the success of STAI Al Badar Cipulus lies in its ability to integrate spiritual values with professional management, providing a model for adaptive and value-based strategic management in Islamic higher education institutions.